2018
DOI: 10.1016/j.toxrep.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Montivipera bornmuelleri venom has immunomodulatory effects mainly up-regulating pro-inflammatory cytokines in the spleens of mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Different biological activities of Montivipera bornmuelleri's venom have been recently described (for review, see Rima et al, 2018). Among these, the selective cytotoxicity of M. bornmuelleri's venom on benign and malignant cells (Sawan et al, 2017) and its upregulation of pro-inflammatory cytokines (Yacoub et al, 2018) suggested an anticancer potential of the venom. To further validate this hypothesis, this study was conducted to dissect the cytotoxicity of M. bornmuelleri's crude venom on cancer cell lines and its effect on tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different biological activities of Montivipera bornmuelleri's venom have been recently described (for review, see Rima et al, 2018). Among these, the selective cytotoxicity of M. bornmuelleri's venom on benign and malignant cells (Sawan et al, 2017) and its upregulation of pro-inflammatory cytokines (Yacoub et al, 2018) suggested an anticancer potential of the venom. To further validate this hypothesis, this study was conducted to dissect the cytotoxicity of M. bornmuelleri's crude venom on cancer cell lines and its effect on tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To further validate this hypothesis, this study was conducted to dissect the cytotoxicity of M. bornmuelleri's crude venom on cancer cell lines and its effect on tumor growth in vivo. We started our experimental approach by checking whether the impact of M. bornmuelleri's venom on pro-inflammatory cytokines levels described previously (Yacoub et al, 2018) is due to endotoxins within the venom. In fact, endotoxins are found on the outer membrane of most gram-negative bacteria (Raetz, 1990) and are known as strong inducers of the immune system (Singh & Jiang, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low number of studies on the characterization of the inflammatory process involved in the snake envenomation of the Viperinae subfamily, which includes the genus Bitis, a recent work was published showing the pro-inflammatory activity of the Montivipera bornmuelleri venom using a peritonitis mice model. After 6 h and 24 h of venom inoculation, the production of TNF-α, IFN-γ, IL-1β, IL-17, IL-4 and IL-10 were detected [25]. In another study, after treating U937 cells with Vipera ammodytes ammodytes venom, an increase in the expression of several inflammatory genes was observed, such as IL-1β and IL-8 [26].…”
Section: Introductionmentioning
confidence: 93%
“…These experiments are now feasible since the toxicity of the venom has been recently identified in vivo [ 62 ]. More recently, the immunomodulatory effects of M. bornmuelleri venom in vivo on the splenic levels of tumor necrosis factor, TNF-α; Interferon IFN-γ; and Interleukins, IL-4, IL-10, IL-1β, and IL-17 have been studied in vivo [ 63 ]. In fact, M. bornmuelleri venom up-regulated the levels of the pro-inflammatory cytokines, TNF-α, IFN-γ, IL-1β, and IL-17, and established a trend in decreasing the anti-inflammatory cytokine, IL-10.…”
Section: Montivipera Bornmuellerimentioning
confidence: 99%